Humidity responsive actuation of bioinspired hygromorph biocomposites (HBC) for adaptive structures. (January 2019) - Le Duigou, Antoine; Keryvin, Vincent; Beaugrand, Johnny; Pernes, Miguel; Scarpa, Fabrizio; Castro, Mickael
Abstract: Hygromorph biocomposites (HBC) possess moisture-induced actuation from bioinspired designs. The present work describes a large experimental and comprehensive database of the hygro-mechanical and bending actuation properties of flax/maleic anhydride grafted polypropylene (MAPP) HBC composites over a large range of moisture variation (10–90% RH) and water immersion. HBCs exhibit a promising responsiveness and reactivity over the whole relative humidity range (10–90% RH), with acceleration and increase of the actuation observed as soon as a 30% RH value is reached. The experimental data are compared to analogous results from an analytical model based on a modified Timoshenko theory, and a finite element model based on the use of classical laminate theory (CLT). We discuss the effects of the hygroscopic properties (β coefficient) and the design parameters (length/width and thickness ratios) of the composites on the actuation performance.